Wind Speed Analysis Study for Wind Power Plant in Kebumen - Tafrikhatin, Asni; Purnata, Hendi; Hafid Kusuma , Rafli; Faisal Efendi , Anggi; Mahfud, Guffaro (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Reserves of fossil energy sources are starting to run low, so the government has launched renewable energy sources. The National Energy Policy (KEN) targets Indonesia by 2025 to use renewable energy sources of 23% of its energy needs. Because of this, the government has started opening places that have the potential for generating renewable energy, especially the areas where PLN electricity cannot reach, withincluding the southern coastal area of Kebumen.. The wind potential in this coastal area of Java Island meets the criteria for a Wind Power Plant. The purpose of this research was to analyze the wind potential in the southern coastal area of Kebumen. The specific purpose of this study was to determine the wind speed and the location and calculate the power generated by the wind in the southern coastal area of Kebumen to determine the potential of PLTB in Kebumen area. The stages of this research consisted of retrieval of secondary data, analysis using Excel, and power analysis using HOMER. Based on wind speed data from NASA, the southern coastal area of Kebumen is suitable for making PLTB, especially Buayan and Ayah, because the wind speed between 2016-2020 is 2.15 m/s. Then, the power produced annually in these places, based on the HOMER application, was 86.50 kWh/year.